2021
DOI: 10.3390/ijms22042083
|View full text |Cite
|
Sign up to set email alerts
|

6,7,4′-Trihydroxyflavanone Protects against Dextran Sulfate Sodium-Induced Colitis by Regulating the Activity of T Cells and Colon Cells In Vivo

Abstract: Colitis is a multifactorial disorder that mostly occurs in the gastrointestinal tract. Despite improvements in mucosal inflammation research, little is known regarding the small bioactive molecules that are beneficial for regulating T cells and colon cell activity. 6,7,4′-trihydroxyflavanone (THF) is a flavanone that possesses anti-osteoclastogenesis activity and exerts protective effects against methamphetamine-induced immunotoxicity. Whether THF mitigates intestinal inflammation by regulating T cells and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[29] There are also studies showing no correlation between weight loss and prognosis of colon cancer, and most of these studies were also analyzed based on the presence or absence of weight loss, without statistical information such as the specific degree of reduction included in the analysis, which is consistent with the conclusion we reached in this study, so it is considered that the degree of weight loss is more significant in patients with advanced cancer, and early stage patients can also show weight loss as a manifestation, but to a lesser extent. [30] The presence or absence of weight loss is not a prognostic influence, while severe weight loss has a correlation with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[29] There are also studies showing no correlation between weight loss and prognosis of colon cancer, and most of these studies were also analyzed based on the presence or absence of weight loss, without statistical information such as the specific degree of reduction included in the analysis, which is consistent with the conclusion we reached in this study, so it is considered that the degree of weight loss is more significant in patients with advanced cancer, and early stage patients can also show weight loss as a manifestation, but to a lesser extent. [30] The presence or absence of weight loss is not a prognostic influence, while severe weight loss has a correlation with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,4′-trihydroxyflavanone (THF, C 15 H 12 O 5 ), a bioactive molecule of the flavanone family, is isolated from Dalbergia odorifera (Leguminosae) [ 23 ] and has been traditionally used for its anti-epigastric pain, anti-rheumatic, anti-ischemic, and anti-swelling properties [ 24 ]. Recent reports have shown that THF possesses several bioactivities against osteoclastogenesis in bone formation, exerting anti-inflammatory effects against dextran sodium sulfate (DSS)-induced immune bowel disease (IBD) and protective effects against hypoxia-induced neurotoxicity via the enhancement of the Nrf2/HO-1 signaling pathway [ 23 , 25 ]. In particular, the ameliorative effect of THF on METH-induced cytotoxicity has been studied in T cells, where pretreatment with THF significantly restored the METH-induced deactivation of T cells under stimulated conditions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%